Penatalaksanaan Cedera Muskuloskeletal pada Korban Kecelakaan melalui Simulasi Evaluasi pada Masyarakat Awam - Sugiyarto Sugiyarto; Akhmad Rifai (Universitas Islam Jember, 2022)
Musculoskeletal injury is an injury to one part of the musculoskeletal system that can be acute or as a result of gradual overuse which usually causes dysfunction of surrounding structures and the structures that are protected or supported, resulting in not being able to function properly in muscles, tendons, ligaments, joints or bones. The general purpose of this study was to determine the level of cedar musculoskeletal management skills in accident victims in the general public. This research is an experimental study with a Pre-Test-Post Test one Group design approach. Through testing research hypotheses. The population of this research is the cloud community totaling 48 respondents. Paired statistical test using nonparametric Wilcoxon test. Based on the results of the Wilcoxon analysis test, it can be concluded that 48 respondents who received training in the management of musculoskeletal injuries in accident victims through evaluation simulations in the general public can be concluded that the majority of ordinary people have good knowledge in terms of the ability to handle musculoskeletal injuries in accident victims through evaluation simulations. with a p value of 0.001 which means that there is a significant difference between before and after training with simulation. Education and training on musculoskeletal injury management actions for accident victims through evaluation simulations in the general public continues to be held to improve the ability of these action skills